Antenna selection in massive mimo based on matching pursuit - Mendonça, Marcele Oliveira Kuhfuss de (2018)
As wireless services proliferate, the demand for available spectrum also grows. As a result, the spectral efficiency is still an issue addressed by many researchers looking for solutions to provide quality of service to a growing number of users. massive MIMO is an attractive technology for the next wireless systems since it can alleviate the expected spectral shortage. This work proposes two antenna selection strategies to be applied in the downlink of a massive MIMO system, aiming at reducing the transmission power. The proposed algorithms can also be employed to select a subset of active sensors in centralized sensor networks. The proposed strategy to select the antennas is inspired by the matching pursuit technique. The presented results show that an efficient selection can be obtained with reduced computational complexity.